Recent Advances in Methods of Puerarin Biotransformation - Liu, Guiyou; Liu, Zhonghua; Yuan, Sheng (Mini Reviews in Medicinal Chemistry, 2016)
Puerarin is an isoflavonoid extracted from the roots of Pueraria lobata in the Pueraria thomsonii family. Puerarin displays a broad range of pharmacological activities and has been widely used in clinics. However, puerarin’s low solubility and permeability result in poor gastrointestinal absorption and low bioavailability. Simply increasing the dose does not effectively increase bioavailability and might lead to toxicity and side effects. Considerable progress has been achieved in the recent years on puerarin structural biotransformation using microorganisms and free enzymes. Increasingly numerous new puerarin derivatives with high solubility and bioactivity have been developed. This paper reviews recent progress in the biotransformation of puerarin.
Keywords: Deglycosylation